The Marketer's Dilemma: Focusing on a Target or a Demographic? - Hess, Mike; Doe, Pete (Journal of Advertising Research, 2013)
Data-integration techniques can be useful tools as marketers continue to improve overall efficiency and return on investment. This is true because of the value of the techniques themselves and also because the current advertising market, based on demographic buying, has major opportunities for arbitrage in the range of 10 percent to 25 percent (where in that range depends on the nature of the vertical). The current study reviews different methods of data integration in pursuing such negotiations.